INVESTIGATION OF THE EFFECT OF DEMOGRAPHIC CHARACTERISTICS OF DECOMPOSİTİON, DİSPATCH AND DISTRIBUTION EMPLOYEES IN POSTAGE WORKS ON LEVELS OF ORGANIZATIONAL COMMITMENT - Topal, Ali (International Journal of Research -GRANTHAALAYAH, 2021)
The aim of the research is to determine the demographic characteristics of the employees who make decomposition, dispatch and distribution in the postal works; is to determine at what level it affects organizational commitment levels. The population of the research consists of 2703 people who make decomposition, dispatch and distribution in postal works in Ankara province. The sample consists of 238 volunteers, 122 of whom are male and 116 are females. Data and information were collected by applying the organizational commitment scale developed by Meyer, Allen, and Smith and the questionnaire with 7 demographic questions in October, November and December 2018, and in January, February and March 2019. There is one main hypothesis and seven sub-hypotheses in the research. Normality, skewness and kurtosis test, t test from hypothesis tests and ANOVA test from variance analysis techniques were used in the research. As a result of the analyzes applied, it has been seen that the demographic characteristics of the employees who make decomposition, dispatch and distribution in the postal works play an effective role on organizational commitment.